(untitled) (International journal of artificial intelligence, 2026)
Generative artificial intelligence (GenAI) is changing how businesses approach content marketing. Tools like GPT-4, Claude, and Gemini allow companies to create content faster, at lower cost, and with more personalization than ever before. This paper examines the current application of these tools in content marketing, their advantages, drawbacks, and potential future directions. The research draws on industry surveys, academic studies, and reports from leading organizations such as McKinsey, HubSpot, and Grand View Research. Despite the fact that GenAI offers tangible and measurable gains in efficiency, its responsible use necessitates honest communication with audiences, human oversight, and clear editorial standards. The paper also considers what these trends mean for fast-growing digital markets like Uzbekistan.